On classifiers and proper names - Alexandra Cornilescu (Bucharest Working Papers in Linguistics, 2007)
The paper discusses the functional structure of proper names (PNs) in relation to descriptive PNs, verbs of naming, and non-literal uses of PNs. We propose that the functional structure of PNs includes not only a D [+def, j, +Person], but also a qualitative classifier. This proposal reflects the intuition that a complete understanding of a PN requires identifying the kind of entity that it names. The hypothesis of a classifier in the functional structure of PNs provides a natural analysis for descriptive PNs (e.g. Regina Victoria) since, with descriptive PNs, the otherwise silent classifier head is overt. Secondly, we argue that in the naming constructions PNs are mentioned, not used. The function is signalled by the presence of a [name] classifier in the structure of the PN. This analysis allows us to treat PNs as referring expressions, specifically as constants in all their uses. Finally, classifiers are also helpful in interpreting non-literal uses of PNs, since they mostly involve formation of a new category or class, prototypically represented by the literal referent of the PN. The information supplied by the classifier is instrumental in this type inference.